Efeitos na aprendizagem para auditoria interna na mitigação do risco de corrupção nas empresas envolvidas com a Operação Lava Jato - Santos, Antonio Edson Maciel dos (2019)
Purpose: The objective of this study was to identify the learning effects for Internal Audit in mitigating the risk of corruption in the companies involved in the Lava Jato Operation, comparing before and after the event. The main references researched were: Organizational Learning and Culture, Corporate Fraud, Corruption, Lava Jato Operation, Internal Auditing, Governance, Risk and Compliance. The study is based on authors and references such as: Argyris and Schon, Abramo and Institute of Internal Auditors (IIA), Transparency International (TI), Federal Public Ministry (MPF) and the Brazilian Institute of Corporate Governance (IBGC). Design/methodology/approach: The method used to conduct the research was characterized in an explanatory research with a qualitative approach, performed with managers responsible of the Internal Auditors of the companies involved in the Lava Jato Operation, the data were collected through semi-structured and unstructured interviews and for the interpretation of the interviews content analysis was used. In view of the research. Results: its results showed that the main learning effects for Internal Audits were: (i) greater focus on mitigating the risk of corruption; (ii) prioritization of investments in people, training and technology; qualification of Internal Auditing and (iv) creation of business opportunity. Moreover, the Internal Auditing was independent in its activities, as well as the objectivity of his managers. When the subject is preparing for risk mitigation of corruption, it has been noted that Internal Auditing have had relevant preparation, but there are still opportunities for improvement. When compared to the practice of Internal Auditing with the adherence to IPPF - Audit of anti-bribery and anticorruption programs, issued by the IIA, the study points out that this adherence is partial on the part of the companies studied, since the audit of culture was little explored by the companies researched. Practical implications: It is worth highlighting that the issues explored in this study, as well its results, can contribute to the Internal Auditing to be better prepared to help mitigate the corruption risk of their respective organizations, which in practice has resulted in better structured, independent and better prepared audits to mitigate the risk of corruption . Originality/value: In the literature review, no research records were identified that addressed the Internal Auditing learning in cases of corruption. In this sense, the study also offered a scientific contribution and the formulation of new questions to be answered about Internal Auditing.